2007
DOI: 10.2172/920543
|View full text |Cite
|
Sign up to set email alerts
|

Interim Report: Uranium Stabilization Through Polyphosphate Injection - 300 Area Uranium Plume Treatability Demonstration Project

Abstract: SummaryFor fiscal year 2006, the United States Congress authorized $10 million dollars to Hanford for "…analyzing contaminant migration to the Columbia River, and for the introduction of new technology approaches to solving contamination migration issues." These funds are administered through the U.S. Department of Energy Office of Environmental Management (specifically, . After a peer review and selection process, nine projects were selected to meet the objectives of the appropriation. As part of this effort,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 86 publications
1
13
0
Order By: Relevance
“…This suggests that chemical reaction nonequilibrium may influence the migration of polyphosphate compounds. Similar results were previously observed under saturated conditions (Wellman et al 2007c). Possible mechanisms that may have resulted in increased rate-limited sorption are 1) sorption of degradation products onto sedimentbound polymerized phosphate molecules, 2) degradation of polymerized phosphate compounds and subsequent sorption to the sediment matrix, or 3) rapid precipitation of heavy, fast-settling solid phases.…”
Section: Ortho- Pyro- and Tripolyphosphate Transport Under Unsaturasupporting
confidence: 91%
“…This suggests that chemical reaction nonequilibrium may influence the migration of polyphosphate compounds. Similar results were previously observed under saturated conditions (Wellman et al 2007c). Possible mechanisms that may have resulted in increased rate-limited sorption are 1) sorption of degradation products onto sedimentbound polymerized phosphate molecules, 2) degradation of polymerized phosphate compounds and subsequent sorption to the sediment matrix, or 3) rapid precipitation of heavy, fast-settling solid phases.…”
Section: Ortho- Pyro- and Tripolyphosphate Transport Under Unsaturasupporting
confidence: 91%
“…In addition to those noted in previous publications (Wellman et al 2007(Wellman et al , 2008a(Wellman et al , 2011Bovaird et al 2010;Vermeul et al 2009), some limitations of polyphosphate treatment technologies were identified, which impact field scale applicability in different treatment zones. The trend of increased sedimentphosphate contact time resulting in higher phosphate precipitate (and a greater decrease in uranium leaching) implies that polyphosphate injection into groundwater may not deposit sufficient phosphate precipitate due to high groundwater flow (i.e., insufficient contact time).…”
Section: Conclusion and Challengesmentioning
confidence: 73%
“…Although most contaminated sediment from the highly contaminated ponds was removed in the early 1990s, uranium continues to leach from variably saturated (i.e., smear zone) sediments beneath the original ponds seasonally and is the largest source of uranium in groundwater that eventually advects into the Columbia River (Catalano et al 2008;Bond et al 2008;Liu et al, 2008). The use of phosphate treatment of sediments has been shown to effectively decrease uranium leaching short-term column experiments (Shi et al 2009) and in numerous batch and one-dimensional (1-D) column studies (Wellman et al 2006a(Wellman et al , 2006b(Wellman et al , 2007(Wellman et al , 2008a(Wellman et al , 2008b(Wellman et al , 2011Bovaird et al 2010). However, a field-scale groundwater injection of a phosphate solution in the Hanford 300 Area showed limited effectiveness at decreasing uranium concentration in fast flowing groundwater (Wellman et al 2011;Vermeul et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These values were adjusted for field conditions assuming that retardation was due to the <2-mm fraction and that the <2-mm fraction composed ~10% of the total sediment matrix. The field K d and retardation values were calculated using a porosity value of 0.2 and bulk density value of 2.19 g/cm 3 , which were quantified within the limited field investigation (LFI) ( Table 2.3) (Wellman et al 2007). Sorption of phosphate and calcium to the sedimentary matrix is relatively slow, requiring several hours.…”
Section: High Flow Velocitiesmentioning
confidence: 99%
“…The limited retardation observed under field conditions limited the mixing of the three remedy phases. Furthermore, Wellman et al (2007) previously noted that the ratio of calcium to phosphate needed to precipitate apatite is highly sensitive. The highly variable hydrodynamic conditions present in the 300 Area subsurface challenge the ability to control this variable.…”
Section: Low Surface Areamentioning
confidence: 99%